Estado nutricional, grasa corporal y riesgo de diabetes mellitus tipo 2 en adultos atendidos en el Hospital Regional de Loreto, Iquitos 2022 - Sánchez Carranza, Claudia María Alexandra (2024)
The purpose of this research was to analyze patients (Px) who were scheduled for outpatient general medicine consultation at the Loreto Regional Hospital in the year 2022, to determine their nutritional status (NS), body fat percentage and to establish a relationship between both factors and their potential risk of developing type 2 diabetes mellitus (DM2). The research had a quantitative methodology with a descriptive, non-experimental, cross-sectional and correlational design. The sample consisted of 365 patients, and the instruments were a nutritional status card, a body fat card and the Findrisk test, which were developed by direct interview. The data were analyzed descriptively with bivariate and inferential statistics using Spearman's Rho coefficient. The results show that more than one third of the patients evaluated were overweight and had normal NE, with respect to NE according to abdominal perimeter (AP), more than 40% of the patients were at risk of developing some type of cardiometabolic disease and more than 50% had obese body fat. Likewise, 31.2% presented a moderate risk of DM2. The analysis of the relationship between the variables shows that there is a statistically significant correlation between nutritional status measured by BMI and body fat with the risk of developing DM2, with correlation values of 0.561 and 0.488, respectively, and a p value of 0.000. The study concludes that it is feasible to measure the risk of developing type 2 diabetes mellitus using anthropometric, biochemical and body fat composition parameters.